Study of suicides in Mangalore region of South Karnataka, India - Kumar, Jayantha; R., Rekha (International Journal of Advances in Medicine, 2019)
Background: To evaluate the various causes of suicides and mental illness of different age groups which enables the patients to commit suicide in both sexes. Methods: The data of suicides was collected from medical records of the different Hospital in Mangalore region of South Karnataka. Results: Total 32 cases of suicides in adults were studied at Mangalore city and district as a whole. The history of suicide was 6(18.7%) was alcoholic, 4(12.5%) were drug addicted (dependent), 5(15.6%) were HIV infected, 3(9.37%) had infertility 4(12.5%) had loss of job, 2(6.25%) had sudden loss of property, 8(25%) had failure in love affair. The clinical manifestations of suicides were (8.25%) had major depression 5(15.6%) had multiple personality disorder. 11(34.3%) were schizophrenic, 6(18.7%) had mood disorders, 2(6.25%) were epileptic. Conclusions: This study of suicides of young adults will be quite helpful to psychiatrist and medico-social workers to take preventive measures to prevents such suicides because suicide is not only social problem, but it is due to abnormal mental state too.